ARRDC4-mediated glycolysis enhances innate immunity to influenza A virus through fructose-1,6-bisphosphate - Yuhan Li; Zhen Wang; Jie Wang; Zhimin Jiang; Mingyue Chen; Hui Ai; Chao Ma; Qi Tong; Litao Liu; Tony Velkov; Honglei Sun; Juan Pu; et al. (Proceedings of the National Academy of Sciences, 2025)
Glucose metabolism impacts the innate immune response against viral infection. However, the key enzymes or the natural products and mechanisms involved are not well elucidated. Here, we found that arrestin domain containing 4 (ARRDC4), a critical regulator of glucose metabolism, senses influenza A virus (IAV) infection by interacting with viral PA protein. Upregulated ARRDC4 increases the enzymatic activity of phosphofructokinase, muscle type (PFKM) via binding its His298 site to promote the production of the metabolite fructose-1,6-bisphosphate (FBP). Consequently, FBP inhibits the K48-linked ubiquitination degradation of HSP90β, subsequently enhances its interaction with IKKβ and IKKε, and enhances NF-κB- and IRF7-mediated antiviral innate immunity, respectively. Importantly, FBP supplementation enhanced IFN-β-mediated antiviral innate immunity in vitro and in vivo. Our findings highlight a unique immunometabolic regulatory mechanism in which ARRDC4 senses IAV infection and regulates antiviral innate immunity through the PFKM-FBP metabolic axis and provide a strategy for manipulating FBP-related metabolism to treat viral infection.